2007
DOI: 10.4049/jimmunol.178.3.1581
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-Independent Costimulation of IL-10 Secretion by SDF-1/CXCL12 Proceeds via AP-1 Binding to the Human IL-10 Promoter

Abstract: Costimulation by the chemokine, stromal cell-derived factor-1 (SDF-1)/CXCL12, has been shown to increase the amount of IL-10 secreted by TCR-stimulated human T cells; however, the molecular mechanisms of this response are unknown. Knowledge of this signaling pathway may be useful because extensive evidence indicates that deficient IL-10 secretion promotes autoimmunity. The human IL-10 locus is highly polymorphic. We report in this study that SDF-1 costimulates IL-10 secretion from T cells containing all three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 63 publications
3
32
0
Order By: Relevance
“…23 Conversely, other reports suggested that the presence of a G-allele at À1087 was associated with an increase in the IL-10 promoter activity. 24,25,28,29 In earlier studies from our laboratory, 30,31 we demonstrated that severe chronic periodontitis was strongly associated with the GG genotype of the À1087 IL-10 gene polymorphism and that the GG genotype correlated with enhanced fractions of IL-10-positive cells in periodontitis lesions.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…23 Conversely, other reports suggested that the presence of a G-allele at À1087 was associated with an increase in the IL-10 promoter activity. 24,25,28,29 In earlier studies from our laboratory, 30,31 we demonstrated that severe chronic periodontitis was strongly associated with the GG genotype of the À1087 IL-10 gene polymorphism and that the GG genotype correlated with enhanced fractions of IL-10-positive cells in periodontitis lesions.…”
Section: Introductionmentioning
confidence: 75%
“…25,28 Transcriptional regulation of the IL-10 gene was studied in several cell types, 23,24,29,33 but the results regarding the influence of the À1087 polymorphism on IL-10 gene expression are conflicting. Rees et al 23 using transient transfections in an Epstein-Barr virustransformed human B-cell line showed that the A-allele was associated with a twofold increase in transcriptional activity as compared to the G-allele.…”
Section: Sp1 Transcription Factor Binds To the Il-10 à1087 G-allele Lmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20,26,27,32 The present series of experiments were performed to study the influence of the binding of the Sp1 transcription factor to the À1087 SNP on IL-10 transcription. The binding of the transcription factors PU.1, Spi-B and Sp1 to this site in the IL-10 promoter was earlier analyzed using electromobility shift assay.…”
Section: Discussionmentioning
confidence: 99%
“…19,[25][26][27]32,40,41 Thus, Turner et al 27 found that subjects who were negative for the A allele exhibited a higher production of IL-10 than subjects who were positive for the A allele. These results are in concordance with data presented in a study on stimulated purified blood lymphocytes.…”
Section: Discussionmentioning
confidence: 99%